Tinjauan observasional terhadap dinamika lingkungan sekolah MTsN 2 Malang: Pendekatan untuk peningkatan kualitas pembelajaran - Fitri, Rahmania Lailatul (Maliki Interdisciplinary Journal, 2024)
Improving the quality of learning has become a main focus in the world of education due to recognition of its important role in creating a more developed and empowered society. Effective learning not only impacts students' academic performance, but also impacts their ability to think critically, problem solve, communicate, and collaborate – skills necessary in an ever-changing world. Therefore, approaches to improving the quality of learning are an important aspect in efforts to prepare a competent and resilient future generation.